2015
DOI: 10.1177/1687814015572457
|View full text |Cite
|
Sign up to set email alerts
|

Finite element method study on the influence of initial stress on machining process

Abstract: Machining-induced residual stress has significant influence on the performance of the parts. Extensive studies about machining-induced residual stress concerning many factors have been carried out but few focused on the role of initial stress distribution in cutting process. In this study, a finite element method study on the influence of initial stress on machining process is carried out. A combined method to obtain the parameters in Johnson-Cook constitutive model was introduced and verified with face millin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The chip morphology, the cutting force, and heat are easily obtained in the simulation software, and the method for getting the circumferential residual stress is detailed in Ma et al [17].…”
Section: Methodsmentioning
confidence: 99%
“…The chip morphology, the cutting force, and heat are easily obtained in the simulation software, and the method for getting the circumferential residual stress is detailed in Ma et al [17].…”
Section: Methodsmentioning
confidence: 99%
“…[16] have used a simplified analytical model of the cutting loads and stress-strain zone during cutting process based on research conducted by Ma, Feng, Zhang, Wu, & Yu (2016) [17]. Ma, Yu, Feng, Wu, & Zhang, (2015) [18] used a Finite Element Method (FEM) model and showed that initial tensile stress makes the cutting stress distribution within the workpiece become more tensile. This condition is caused by thermal effect from the cutting temperature.…”
Section: Introductionmentioning
confidence: 99%
“…This study is further studied by Ma et al [8] as they have simplified analytical model of the cutting loads and stress zone during cutting process. Ma et al [9] used a Finite Element Method (FEM) model and showed that initial tensile stress makes the cutting stress distribution within the workpiece become more tensile and diminishes the cutting forces and tool tip temperature.…”
Section: Introductionmentioning
confidence: 99%